Motility in Echinosphaerium nucleofilum. I. An analysis of particle motions in the axopodia and a direct test of the involvement of the axoneme (The Rockefeller University Press, 1975)
The motion of particles in the axopodia of Echinosphaerium nucleofilum is saltatory. In the present study, photokymograph records of 123 motions from six axopodia have been analyzed. Particles followed rectilinear paths of from 1 to 15 mum while in continuous motion at an average velocity of 0.66 plus or minus 0.32 mum/s. The velocity of the particles was variable in 36% of the cases measured. Some motions were punctuated by pauses either before continuing in the same direction or reversing. Frequently, several particles were moving at the same velocity, but neighboring particles showed no motion or moved in the opposite direction. Two particles occasionally contacted one another and travelled as a unit for varying lengths of time but subsequently moved independently. These motions reflect the underlying mechanism of motive force production. Furthermore, a glass microneedle can be substituted for the microtubular axoneme in the axopodia. In these artificial axopodia, bidirectional particle motions occurred which were similar to those in normal axopodia. Colchicine, at the threshold dose for axonemal dissolution, had no affect on these particel motions. It is concluded that the microtubular axoneme is not responsible for particle motions and also that individual microtubules are unlikely candidates for motive force production in this system.